GINGER WRITER AS AN ONLINE REPHRASE TOOL WITH AI-POWERED SUGGESTIONS OF ALTERNATIVE SENTENCES IN ENGLISH WRITING - Tira Nur Fitria (Leksema: Jurnal Bahasa dan Sastra, 2023)
This is a descriptive-qualitative study analyzes the use of Ginger Writer as an online rephrase tool based on AI-powered suggestions in English writing. The result of analysis shows that the free edition of the Ginger Writer application is used for the implementation. Some techniques of rephrasing applied b the tools are: (1) rephrasing by using equations/synonyms of words. (2) rephrasing by changing/rearranging the sequence of words based on the relevant rules. (3) rephrasing by altering the word's form, (4) rephrasing by using the active or passive form, (5) rephrasing by changing the word class, and (6) rephrasing word into phrase, phrase into clause, and vice versa. Ginger Writer makes writing high-quality work effortless for users. Not only adds missing words, completes fragmented phrases, and corrects spelling problems related to the context of sentences, Ginger Writer also adds missing words, completes fragmented sentences, and corrects spelling errors. This online rephrasing tool is considerably fast but teachers and students should double-check their work. To some extent, manual paraphrasing is considered better and, even the best in quality, compared to the automatic ones.